2021 Proceedings of the Conference on Control and Its Applications 2021
DOI: 10.1137/1.9781611976847.1
|View full text |Cite
|
Sign up to set email alerts
|

Error Bounds for Carleman Linearization of General Nonlinear Systems

Abstract: In his 1932 paper, Carleman proposed a linearization method to transform a given finite-dimensional nonlinear system with analytic right-hand into an equivalent infinitedimensional linear system with (usually) unbounded operators. Finite truncation of the transformed system has been used to study dynamic properties, learning, and control of nonlinear systems. One of the remaining outstanding problems in this context is quantifying the effectiveness of such finitely truncated models. Intuitively, one expects th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Recently, Amini et al [69] showed that the error of the Carleman linearization can be bounded exponentially by the truncation order N , but this statement does not hold for any arbitrary time. As is clearly described in the paper, provided with the assumption that the flow field can be approximated by a Maclaurin expansion, the error for a sufficiently short horizon is exponentially bounded.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Recently, Amini et al [69] showed that the error of the Carleman linearization can be bounded exponentially by the truncation order N , but this statement does not hold for any arbitrary time. As is clearly described in the paper, provided with the assumption that the flow field can be approximated by a Maclaurin expansion, the error for a sufficiently short horizon is exponentially bounded.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…The problem, as formulated above, is difficult to solve for general nonlinear systems. In this paper, inspired by [10], the formulation is restricted to a sub-class of nonlinear systems, defined by the following assumptions. Assumption 1.…”
Section: Problem Statementmentioning
confidence: 99%
“…While this assumption is restrictive, a large subclass of systems fall under this category, since polynomial, trigonometric, and exponential functions have Maclaurin expansions with exponential decay. The idea is to use Carleman lifting [9], [10] to lift the nonlinear system into an infinite-dimensional linear system such that the truncation of the trajectory of the linear system to the first d dimensions approximates the trajectory of the system in (1), in infinity norm. The infinite-dimensional linear system is then truncated to yield a finite-dimensional linear system such that the error between the projected trajectories and the original trajectories is less than the given error bound, ∆.…”
Section: Problem Statementmentioning
confidence: 99%
See 2 more Smart Citations